A study on factors influencing social media addiction among public university students in Malaysia / Nurul Haziqah Zainal and Nurul Izzah Khairul Anuar - Zainal, Nurul Haziqah (2022)
On the year of 2021, the users of social media in Malaysian had increased to 28 million which made Malaysia be ranked as the ninth most active country in the world on social media. The use of social media had led more to negative effects rather than positive effects. Once the students spend too much time on social media it will distract the learning process and affecting the student’s academic performance as the addiction can cause them to face a health problem. Hence, the objective of this research is to identify the factors that lead to social media addiction among students in public universities in Malaysia. For this purpose, a survey was conducted towards 384 respondents by using a quantitative survey to determine the relationship between accessibility of internet, social media as reference material and lack of time management and control over the usage with social media addiction. The hypotheses are then proposed and tested using Pearson Correlation. Thus, the analysis reveals that all the independent variables had a relationship with social media addiction (accessibility of internet: r = 0.232**, p = 0.000; social media as reference material: r = 0.327**, p = 0.000; lack of time management and control over the usage: r = 0.535**, p = 0.000). Thereby, our findings indicate all of the independent variables had a connection and influence the factor to social media addiction.